2007
DOI: 10.1364/oe.15.002940
|View full text |Cite
|
Sign up to set email alerts
|

Generation of supercontinuum bottle beam using an axicon

Abstract: A supercontinuum bottle beam was successfully produced by focusing a supercontinuum laser beam after passing through an axicon. The supercontinuum radiation was generated from a microstructured fiber pumped by a self-kerr-lens mode-locked femtosecond Ti:sapphire laser. The cross-section intensity distributions of the generated bottle were recorded by a beam profiler. Using the line filters to select different central wavelengths, the different colors of bottle beams show slightly different bottle ranges and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Monochromatic BLB are most often produced by methods based on annular diaphragms and lenses [7], as well as on axicons [8]. When these methods are used to create ultrashort Bessel light pulses (BLP), distortions of the pulse envelope owing to dispersion can have a significant effect.…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations
“…Monochromatic BLB are most often produced by methods based on annular diaphragms and lenses [7], as well as on axicons [8]. When these methods are used to create ultrashort Bessel light pulses (BLP), distortions of the pulse envelope owing to dispersion can have a significant effect.…”
Section: 42mentioning
confidence: 99%
“…At the same time, there have been few studies of pulsed Bessel light fields made up of a superposition of BLB whose frequencies lie within a certain interval. These fields can combine the advantages of monochromatic BLB and ultrashort pulses with a high local luminous energy, so they offer some promise for use in ranging systems, for controlling electrical discharges [5], and for forming cluster plasmas [6].Monochromatic BLB are most often produced by methods based on annular diaphragms and lenses [7], as well as on axicons [8]. When these methods are used to create ultrashort Bessel light pulses (BLP), distortions of the pulse envelope owing to dispersion can have a significant effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Axicons and their combinations can be used for many applications, and for the first time this came to attention in [1], where a number of specific schemes is considered as well. In particular, a variety of papers are devoted to the calculation and analysis of a focusing scheme consisting of a thin lens and an axicon [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This combination can be used to obtain a high-quality focal ring.…”
Section: Introductionmentioning
confidence: 99%
“…The axiconlens system is also of interest in the context of feasibility to form an unusual axial distribution of intensities. It is found that, for a certain choice of the Fresnel number of an optical scheme and diameter of the Bessel beam, the axial intensity distribution is characterized by the existence of two distinct foci located to the left and to the right of the geometrical back focal plane [4,8,10,12,14,16].…”
Section: Introductionmentioning
confidence: 99%